Kinematic and kinetic analysis of counter movement jump versus two different types of standing back somersault - Mkaouer, B.; Jemni, M.; Amara, S.; Chaabèn, H.; Tabka, Z. (Science of Gymnastics Journal, 2012)
The aim of this study was to compare the take-off`s kinetic and kinematic variables between three types of jumps from a standing position: counter movement jump with arm swing (CMJa), standing back somersault with landings on the spot (BSls) and standing back somersault with rear displacement at landing (BSld). Five elite level male gymnasts (age 23.17 ± 1.61 years; height 165.0 ± 5.4 cm; weight 56.80 ± 7.66 kg) took part in this investigation. A force plate and a 3D movement analysis system were synchronized and used for data collection. Statistical analysis via non-parametric Kruskal-Wallis test showed a significant difference between the take-off variables. The vertical component of force, peak power, impulse and displacement of the centre of mass were significantly different (P<0.01). Similarly, the horizontal component of force, maximum speed, peak power and displacement of the centre of mass were significantly different (P<0.01). However, vertical velocity remained relatively constant. In conclusion, the standing back somersaults performed on the spot`s variables (without back displacement) were very similar to the ones analysed during counter movement jump with arm swing. The standing back somersault with landing on the spot allowed better force impulse. This was facilitated by a take-off closer to the centre of mass, unlike the standing back somersault with rear displacement in landing. Analysing kinetic and kinematic together, allowed the endorsement of linear regression equations enabling the prediction of some variables from others.